Learning processes and learning problems in German postgraduate medical education - van den Bussche, Hendrik; Krause-Solberg, Lea; Scherer, Martin; Ziegler, Stine (GMS Journal for Medical Education, 2017)
Objective: In order to evaluate the quality of postgraduate medical education in Germany, we examined how the learning of theoretical and practical competencies is conceptualized and how the learning process takes place in real terms. The training conditions, as perceived by medical residents, are compared with the learning objectives, as stated by the Federal Chamber of Physicians in its regulation on postgraduate education. The analysis is based on the data of the “KarMed” study (abbreviation of "career progression and career breaks among physicians during postgraduate education"), a multicentre cohort study of medical school graduates from seven universities who arre followed until they receive their licenses as specialist physicians. The study was conducted by the Institute of Primary Medical Care of the University Medical Center Hamburg-Eppendorf starting in 2008.Methodology: The KarMed study is based on annual, standardized surveys of the population described above. 48% responded in the initial survey (n=1012) and 85% or more in each of the following surveys. Descriptive statistics and logistical regressions were used for analysis. Gender-specific analyses were performed where possible in order to highlight the differences in the professional objectives and workloads between female and male physicians. Results: The study shows that both the practical and the theoretical components of postgraduate medical education in Germany are insufficient. There is a lack of a curriculum with precise learning objectives and descriptions of the corresponding educational settings. In fact, the act of learning is identical to daily clinical work. There is no structuring of the work process with regard to learning; for example, documentation procedures and feedback discussions are prescribed but largely omitted. Evidence-based medicine is not a systematic part of the training, nor is the evaluation of residents’ progress. The summative final oral examination pretends that the necessary specialist competencies can be evaluated within 30 minutes.Many factors indicate that female doctors, especially those with children, have fewer learning opportunities than male doctors.Conclusion: The quality of postgraduate medical education in Germany has become inadequate, especially in an international comparison. The deficits are well known. The responsible institutions are called upon to implement sustainable reforms in the sense of postgraduate education that is structured according to educational principles and whose quality is assured.